Inflation, large-scale structure and inhomogeneous cosmologies - Nadathur, S (2011)
Determining cosmological parameters from current observational data requires knowledge of the primordial density perturbations generated during inflation. We begin by examining a model of inflation along a flat direction of the minimal supersymmetric Standard Model (MSSM) and the power spectrum of perturbations it can produce. We consider the fine-tuning issues associated with this model and discuss a modification of the potential to include a hybrid transition that reduces the fine-tuning, without affecting the viability of the model. However, supersymmetric flat directions might play a role in other models of inflation as well. In particular, they may cause a feature in the primordial power spectrum of perturbations, unlike the scale-free spectrum assumed in the standard Lambda Cold Dark Matter (LCDM) cosmological model. We then show that in the presence of such a feature, an alternative cosmological model with a large local void and no dark energy provides a good fit to both Type Ia supernovae and the cosmic microwave background (CMB) data from the WMAP satellite. Constraints from the locally measured Hubble parameter, baryon acoustic oscillations and primordial nucleosynthesis are also satisfied. This degeneracy motivates a search for other independent observational tests of LCDM. The integrated Sachs-Wolfe (ISW) imprint of large-scale structure on the CMB is one such test. The ISW imprint of superstructures of size ~100 Mpc/h at redshift z~0.5 has been detected with >4 sigma significance, however it has been noted that the signal is much larger than expected. We revisit the calculation using linear theory predictions in a LCDM cosmology and find the theoretical prediction is inconsistent by >3 sigma with the observation. If the observed signal is indeed due to the ISW effect then huge, extremely underdense voids are far more common in the observed universe than predicted by LCDM.